TRANSFORMATION MANAGEMENT ESG (ENVIRONMENTAL, SOCIAL, GOVERNANCE) BASED FOR SUSTAINABILITY ORGANIZATION (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2025)
ESG-based management transformation (environmental, social, and governance) has become a new paradigm in ensuring organizational sustainability. This article aims to analyze how the implementation of ESG in managerial strategies can enhance the competitiveness and sustainability of organizations. Using descriptive qualitative methods, this research examines various models, obstacles, and solutions in the implementation of ESG. The research results show that the integration of ESG can have a positive impact on the sustainability of the organization, both economically, environmentally, and socially. It was found that the application of ESG principles significantly impacts sustainability performance aspects. These findings underscore the importance of integrating ESG values into managerial practices as an innovative strategy to achieve long-term sustainability.